Different Conspiracy Theories Have Different Psychological and Social Determinants: Comparison of Three Theories About the Origins of the COVID-19 Virus in a Representative Sample of the UK Population - Hartman, Todd K.; Marshall, Michael; Stocks, Thomas V. A.; McKay, Ryan; Bennett, Kate; Butter, Sarah; Gibson Miller, Jilly; Hyland, Philip; Levita, Liat; Martinez, Anton P.; Mason, Liam; McBride, Orla; et al. (Frontiers in Political Science, 2021)
COVID-19 conspiracy theories have proliferated during the global pandemic, and their rapid spread among certain groups may jeopardise the public health response (e.g., undermining motivation to engage in social distancing and willingness to vaccinate against the virus). Using survey data from two waves of a nationally representative, longitudinal study of life in lockdown in the UK (N = 1,406), we analyze the factors associated with belief in three origin theories related to COVID-19, namely that it 1) originated in a meat market in Wuhan, China; 2) was developed in a lab in Wuhan, China; and 3) is caused by 5G mobile networks. Our findings suggest that political-psychological predispositions are strongly associated with belief in conspiracy theories about the virus, though the direction and effect sizes of these predictors vary depending on the specific content of each origin theory. For instance, belief in the Chinese lab conspiracy theory is strongly associated with right-wing authoritarianism (RWA), social dominance orientation (SDO), and general conspiracy ideation, as well less reliable news sources, distrust in scientists, and anxiety about the pandemic. Belief in the 5G network conspiracy theory is strongly associated with SDO, distrust in scientists, while less strongly with conspiracy ideation and information from social networks/media; RWA is strongly negatively associated with belief in the 5G conspiracy theory, with older and more wealthy individuals somewhat less likely to endorse it. The meat market origin theory is predicted by intolerance of uncertainty, ethnocentrism, COVID-19 anxiety, and less so by higher income, while distrust in scientists is negatively associated with this origin story. Finally, belief in COVID-19 conspiracy theories is associated with negative public health behaviours such as unwillingness to social distance and vaccinate against the virus. Crucially, our findings suggest that the specific content of COVID-19 conspiracy theories likely determines which individuals may be most likely to endorse them.